Disease modeling hypertrophic cardiomyopathy using CRISPR/Cas9 genome editing technology in human pluripotent stem cell-derived cardiomyocytes - Mosqueira, Diogo (2018)
Hypertrophic cardiomyopathy (HCM) is a prevalent genetic cardiovascular disease affecting 1:500 individuals whose cardiac function is deteriorated due to thickening of the left ventricle of the heart, mostly owing to mutations in sarcomeric genes. Modeling HCM in vitro using human pluripotent stem cell-derived cardiomyocytes (hPSC-CM) offers promise to further investigate the disease mechanisms, towards the development of effective drugs.